Biochanin A Alleviates Oxidative Stress in Diabetic Rat Skin - Al-Ghamdi, Abeer S.; Abdel-Naim, Ashraf B.; Al-Abbasi, Fahad A. (Journal of Neonatal Surgery, 2025)
Background: Diabetes mellitus is a significant global health issue, frequently leading to skin complications exacerbated by chronic hyperglycemia and associated oxidative stress. Oxidative stress, characterized by increased reactive oxygen species (ROS), reduced antioxidant defenses (e.g., Catalase - CAT), and elevated lipid peroxidation (e.g., Malondialdehyde - MDA), plays a critical role in impairing skin integrity in diabetic individuals. The Nrf2/ARE pathway is a key regulator of cellular antioxidant responses. Biochanin A (BCA), a natural isoflavone, possesses known antioxidant properties. This study aimed to evaluate the efficacy of topically applied Biochanin A in mitigating oxidative stress within the skin tissue of streptozotocin (STZ)-induced diabetic rats. Methods: Diabetes was induced in male Wistar rats using STZ (50 mg/kg, I.P.). Diabetic rats were randomly assigned to receive topical treatment with either a BCA-loaded hydrogel (5% BCA in 1.5% HPMC), vehicle hydrogel (1.5% HPMC), or no treatment for 14 days. A non-diabetic control group was also included. Following the treatment period, skin tissue surrounding a surgical cut was collected. Oxidative stress markers were assessed by measuring MDA levels and CAT activity. The expression of Nrf2 and its downstream target NQO1 was evaluated using immunohistochemistry. Statistical analysis was performed using ANOVA followed by Tukey's post hoc test (p < 0.05). Results: Compared to the normal control group, untreated diabetic rats showed significantly increased MDA levels and significantly decreased CAT activity, Nrf2 expression, and NQO1 expression in skin tissue. Treatment with BCA significantly reduced MDA levels and significantly increased CAT activity compared to both untreated diabetic and vehicle-treated groups. Furthermore, BCA treatment significantly upregulated the expression of Nrf2 and NQO1 compared to untreated diabetic and vehicle-treated groups. The vehicle group showed minimal effects compared to the untreated diabetic group. Conclusion: Topical application of Biochanin A effectively mitigates oxidative stress in the skin of diabetic rats. This protective effect appears to be mediated through the enhancement of antioxidant enzyme activity (CAT), reduction of lipid peroxidation (MDA), and activation of the Nrf2/NQO1 signaling pathway. These findings suggest that BCA holds therapeutic potential for managing oxidative stress-associated skin complications in diabetes.